Major Structural Defects in the Antithrombin Gene in Four Families with Type I Antithrombin Deficiency - Beauchamp, N. J.; Makris, M.; Preston, F. E.; Peake, I. R.; Daly, M. E. (Thrombosis and Haemostasis, 2000)
The molecular basis of quantitative antithrombin deficiency was investigated in four families predicted to have major antithrombin gene rearrangements. A 1,442 bp deletion and insertion of the sequence 5’T(n = 38-40)GAGACG was characterised in one case. Sequence surrounding the breakpoints contained two perfect, and one imperfect, inverted repeats which may have mediated formation of a stem loop structure on one strand during DNA replication potentiating the deletion. A 9,219 bp deletion spanning introns 2 to 5 was identified in a second family. The identical 6 bp sequence was upstream of each breakpoint and the 5’ breakpoint was located in a sequence of the Alu 3 repeat predicted to be susceptible to strand breakage during transcription. This may have promoted misalignment, and deletion, of one of the repeats and the intervening DNA. A novel 1.8 kb antithrombin gene fragment was present in DNA digests from affected members of the third family suggesting a partial antithrombin gene duplication event while in the remaining family, evidence supporting a complete gene deletion was obtained.
Keywords: Antithombin deficiency; major gene defects